Potential applications of dopamine D1 agonist and D2 antagonist LEK-8829 - Živin, Marko (Slovenian veterinary research, 2010)
Ergoline derivative 9,10-Didehydro-N-methyl-(2-propynyl)-6-methyl-8-aminomethylergoline bimaleinate (LEK-8829), possesses dopamine (DA) D1 agonistic and D2 antagonistic properties in the nigrostriatal and mesocorticolimbic DAergic pathways. These unique dual effects have suggested that LEK-8829 could effectively restore previously imbalanced functional linkage between D1 and D2receptors under schizophrenic conditions in which, LEK-8829 could improve both the negative and positive symptoms of schizophrenia. As dopamine D1 receptor agonist, LEK-8829 may also be beneficial in relieving the motor symptoms of parkinsonism, alone, or when co-administered with antiparkinsonic dopamine D2 agonists, such as ergoline derivative bromocriptine. Moreover, antiparkinsonic potential of LEK-8829 may be particularly useful when the treatment of parkinsonism with D2 agonist drugs is complicated by psychosis. Antiparkinsonic properties of LEK-8829 also suggest a lower propensity of the drug for the induction of extrapyramidal syndrome in the treatment of schizophrenia. Furthermore, by blocking dopamine D2 receptors, LEK-8829 could block the incentive for drug-seeking and drug-craving while by stimulating dopamine D1 receptors it could mediate drug reward and gratification. This implies that LEK-8829 could also attenuate the relapse of psychostimulant drug-addiction, while not being addictive by itself. We conclude that agents with LEK-8829-like dual actions toward dopamine receptors, may represent a newand potent drug class for the treatment parkinsonism, schizophrenia and drug-addiction.
Keywords: antipsihotiki; dopaminski antagonisti; Parkinsonova bolezen; podgane; receptorji; shizofrenija; zasvojenost; zdravila